Reduced PLCG1 expression is associated with inferior survival for myelodysplastic syndromes. (21st November 2019) - Shiseki, Masayuki; Ishii, Mayuko; Miyazaki, Mari; Osanai, Satoko; Wang, Yan‐Hua; Yoshinaga, Kentaro; Mori, Naoki; Tanaka, Junji
Abstract: The PLCG1 gene, which encodes the phospholipase C γ1 isoform, is located within the commonly deleted region of the long arm of chromosome 20 (del(20q)) observed in myelodysplastic syndromes (MDS). Phospholipase C is involved in diverse physiological and pathological cellular processes through inositide signaling. We hypothesized that reduced PLCG1 expression because of haploinsufficiency by del(20q) plays a role in the molecular pathogenesis of MDS. Therefore, we analyzed PLCG1 expression in bone marrow mononuclear cells at diagnosis in 116 MDS patients with or without del(20q) by quantitative RT‐PCR to evaluate its clinical significance. The expression level of PLCG1 was significantly lower not only in MDS patients with del(20q) but also in those without del(20q) compared to that of the controls, which suggests that reduced PLCG1 expression is a common molecular event in MDS. Patients in the lowest quartile (Q4) group for PLCG1 expression had lower overall survival (OS) compared to that of other patients (Q1‐Q3) (log‐rank test, P = .0004) with estimated median OS times of 22 in the Q4 group and 106 months in the Q1‐3 group. Univariate and multivariate analysis indicated reduced PLCG1 expression (Q4) was associated with lower OS (hazard ratio 2.58, 95% CI 1.35‐4.84, P = .0049), which suggests that reduced PLCG1 expression is an independent prognostic factor for OS. In addition, patients were well‐stratified for OS by combining PLCG1 expression level (Q4 vs Q1‐3) and bone marrow blast percentage (5% or more vs less than 5%). Thus, the level of PLCG1 expression at time of diagnosis is a prognostic biomarker for MDS. Abstract : We found that reduced PLCG1 expression was associated with worse clinical outcomes, and the level of PLCG1 expression at the time of MDS diagnosis was a useful prognostic marker.